Distinct Mechanisms of Pathogenic DJ-1 Mutations in Mitochondrial Quality Control - Strobbe, Daniela; Robinson, Alexis A.; Harvey, Kirsten; Rossi, Lara; Ferraina, Caterina; de Biase, Valerio; Rodolfo, Carlo; Harvey, Robert J.; Campanella, Michelangelo (Frontiers in Molecular Neuroscience, 2018)
The deglycase and chaperone protein DJ-1 is pivotal for cellular oxidative stress responses and mitochondrial quality control. Mutations in PARK7, encoding DJ-1, are associated with early-onset familial Parkinson’s disease (PD) and lead to pathological oxidative stress and/or disrupted protein degradation by the proteasome. The aim of this study was to gain insights into the pathogenic mechanisms of selected DJ-1 missense mutations, by characterizing protein-protein interactions, core parameters of mitochondrial function, quality control regulation via autophagy and cellular death following dopamine accumulation. We report that the DJ-1M26I mutant influences DJ-1 interactions with SUMO-1, in turn enhancing removal of mitochondria and conferring increased cellular susceptibility to dopamine toxicity. By contrast, the DJ-1D149A mutant does not influence mitophagy, but instead impairs Ca2+ dynamics and free radical homeostasis by disrupting DJ-1 interactions with a mitochondrial accessory protein known as DJ-1 binding protein (DJBP/EFCAB6). Thus, individual DJ-1 mutations have different effects on mitochondrial function and quality control, implying mutation-specific pathomechanisms converging on impaired mitochondrial homeostasis.